Successful Therapy on Patients with Yolksac and Embrional Carcinoma by Surgery and Chemotherapy - Prasetya, Fahmi Adhi; Djajalaksana, Susanthy; Retnani, Diah Prabawati; Isharanto, Artono; Normahayu, Indrastuti; Okta, Shinta (Universitaas Brawijaya, 2020)
Background: Malignant mixed germ cell tumors account for 13-25% of all non seminoma germ cell tumors, almost all cases were found in males (85%), increased in the third decade, and had an average survival rate of 40-45%. With modern management the average 5-year survival rate can be over 80%.Case Report: We reported a case report in Saiful Anwar Malang Hospital, Indonesia, a young man, 26 years old with an malignant epithelial tumor derived from mediastinal or lung. The CT scan of the chest showed an lobulated solid mass of iso-hipodens on the anterior superior mediastinum, mass encompassing the aortic arch, left pulmonalis artery, subclavian artery. The result from transthoracic FNAB with USG guidance showed an malignant epithelial tumor derived from mediastinal or lung, impression of an adeno squamous carcinoma. The AFP, LDH, and NSE serum level was elevated. Patient underwent a surgical sternotomy and tumor debulking. The biopsy showed an malignant mixed germ cell tumor (yolksac and embrional carcinoma). These were confirming the diagnosis of malignant mixed germ cell mediastinal tumor (yolksac and embrinonal carcinoma). Patient received a combination bleomycin, etoposid, cisplatin 3 series chemoteraphy Â and evaluated.Conclusion: Some procedures like biopsy, tumor marker, could differentiate the subtype of mediastinal germ cell tumor. The multimodality treatment by combining surgical therapy (surgical sternotomy and tumor debulking) with chemotherapy could increase the survival rate of patients.